2011
DOI: 10.1097/qad.0b013e3283471deb
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in antiretroviral treatment outcomes among HIV-infected adults in an urban Tanzanian setting

Abstract: Nonadherence to care and advanced immunodeficiency at enrollment explained only 17% of the inferior mortality in HIV-infected men in this resource-limited setting. Additional study of behavioral and biologic factors that may adversely impact treatment outcomes in men is needed to reduce these sex disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 33 publications
13
100
1
1
Order By: Relevance
“…17,18 Given the men's strong preference for HIV clinics as their source of FP services, we argue that integrating FP services into HIV clinics should be kept a priority as this model likely fosters male involvement in FP, which, in turn, may improve contraceptive use. 29 In addition, HIVpositive men in SSA tend to have worse clinical outcomes as compared to women [39][40][41][42][43][44][45] and face unique challenges in accessing and remaining in HIV care and treatment, [46][47][48][49][50] and integrated FP services may serve as one of many tools to attract and retain these men.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Given the men's strong preference for HIV clinics as their source of FP services, we argue that integrating FP services into HIV clinics should be kept a priority as this model likely fosters male involvement in FP, which, in turn, may improve contraceptive use. 29 In addition, HIVpositive men in SSA tend to have worse clinical outcomes as compared to women [39][40][41][42][43][44][45] and face unique challenges in accessing and remaining in HIV care and treatment, [46][47][48][49][50] and integrated FP services may serve as one of many tools to attract and retain these men.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational study was conducted at 12 Management and Development for Health (MDH) HIV care and treatment clinics (CTCs) supported by the U.S. 15,16 For inclusion in these analyses, participants had to be 15 years old and above, not pregnant at the time of enrollment, and have at least two measurements of Hgb concentration.…”
Section: Methodsmentioning
confidence: 99%
“…[3] Men have a higher mortality than women when receiving ART. [4][5][6][7][8] Although the reasons for this are poorly understood, a number of possible explanations have been suggested; some implicitly blame men for their own poorer outcomes. For example, numerous studies have suggested that men's poorer 'health-seeking behaviour' may prevent them from accessing ART services, being adherent to treatment or remaining in care.…”
mentioning
confidence: 99%